The impact of socio-economic policy of Latvia on the preservation of human resources in the context of European integration - Tsaurkubule, Zhanna (Wpływ polityki społeczno-ekonomicznej na zachowanie zasobów ludzkich Łotwy w kontekście integracji europejskiej, 2018)
The article examines the current state of social policy in Latvia and its influence on the preservation of human resources in the country. The analysis is conducted through determining the current state of quantitative and qualitative indicators of socio-economic development of Latvia, as well as through describing social policy in Latvia as part of the social policy of the European Union.The purpose of the research is to analyze the impact of socio- -economic policy on the preservation of human resources in Latvia, as well as to develop thereupon recommendations to improve management of socio-economic processes in the state. Possible courses of action to improve the quality of state regulation measures of social policy in Latvia are reviewed and proposals to increase the effectiveness of the social policy system in Latvia are developed.The research is based on the methodology of the systemic analysis, involving structural-functional approach, which is to highlight structural elements in the system objects and to define their roles (functions) in the system
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 537, s. 119-127
Keywords: Latvia; social policy; socio-economic indicators; human resources; European economic integration; Łotwa; polityka społeczna; wskaźniki społeczno-ekonomiczne; zasoby ludzkie; europejska integracja gospodarcza